2021
DOI: 10.3390/biology10070592
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of NLRP3 (rs4612666) and CARD8 (rs2043211) in Periodontitis and Cardiovascular Diseases

Abstract: Background: The existing data show that inflammasomes play a role in periodontal disease pathogenesis. However, their role in the pathogenesis of periodontitis and coronary heart disease remains unclear. This study had the objective of assessing NLRP3 (rs4612666) and CARD8 (rs2043211) gene polymorphisms in dental plaque and blood of generalized chronic periodontitis (CP) patients in the presence and absence of coronary heart disease (CHD). Methods: A total of 70 subjects were divided into two groups, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…The GP+CHD group showed a higher odds ratio compared to the GP group alone. This is in accordance with the previous study by Mahendra J et al who also demonstrated the significant change in NLRP3 (rs4612666) in cardiac patients with generalized periodontitis compared to non-cardiacs [ 31 ]. The rise in NLRP3 (rs35829419) polymorphism suggests that it recognizes the bacteria indirectly by monitoring the host-derived DAMP levels that are the product of tissue or cell injury caused by bacterial toxins [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…The GP+CHD group showed a higher odds ratio compared to the GP group alone. This is in accordance with the previous study by Mahendra J et al who also demonstrated the significant change in NLRP3 (rs4612666) in cardiac patients with generalized periodontitis compared to non-cardiacs [ 31 ]. The rise in NLRP3 (rs35829419) polymorphism suggests that it recognizes the bacteria indirectly by monitoring the host-derived DAMP levels that are the product of tissue or cell injury caused by bacterial toxins [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…The NLPR3 rs4612666 polymorphism has already been associated with rheumatoid arthritis ( Cheng et al., 2021 ) and cardiovascular diseases ( Mahendra et al., 2021 ). The IL-1β rs1143634 polymorphism is associated with susceptibility to myocardial infarction ( Fang et al., 2018 ), an aggressive phenotype of breast cancer ( Wang and Yuan, 2022 ), and is a predictive factor for a severe course of chronic periodontitis ( Brodzikowska et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%